SWEET POTATO CULTIVATION TECHNOLOGY IN BAGS IN SURAU VILLAGE, TABA PENANJUNG, CENTRAL BENGKULU - W, Widodo; Reny Herawati; Sumardi (Fakultas Pertanian, 2025)
The implementation of community service activities in Surau Village involves the academic community including lecturers and postgraduate students. This implementation was carried out in the form of lectures and discussions between the service team and Surau village residents. This community service is related to the welfare and food security of residents in Surau village which needs to be improved. Counseling and practice of planting sweet potatoes in sacks was carried out jointly between the service team with the participation of mothers from Surau Village. Surau village residents are enthusiastic and enthusiastic about participating in community service development activities carried out by lecturers and postgraduate students from the Agroecotechnology Masters Study Program. In this activity the service team brought sacks containing planting media and sweet potato seeds. The sack containing the planting medium is perforated at several points which represent the distance between the plants when planted in the raised bed. In addition to having holes prepared at points for planting sweet potato stems, the sacks are also provided with holes in which mineral water bottles have been installed and holes have been prepared to drain the water if conditions are not rainy. In practice, planting sweet potato stems is very easy and fun and when the sweet potatoes start to grow they can be used as ornamental plants in the yards of the residents of Surau Village.